The effects of vegetation type on ecosystem carbon storage and distribution in subtropical plantations - Huang, Wei-Qi; Xu, Bin; Chen, Fu-Sheng; Zong, Ying-Ying; Duan, Xiao-Qing; Zhang, Guang-Xin; Wu, Zi-Jun; Fang, Xiang-Min (Frontiers in Forests and Global Change, 2023)
Establishing plantation forests significantly increases the carbon (C) storage of terrestrial ecosystems. However, how vegetation types affect the ecosystem C sequestration capacity is not completely clear. Here, a slash pine plantation (SPP), a Schima superba plantation (SSP) and a Masson pine plantation (MPP), which have been planted for 30 years, were selected in subtropical China. The C storage and distribution patterns of plant, litter and soil were investigated and calculated. The ecosystem C density was 17.7, 21.6 and 15.3 kg m-2 for SPP, SSP and MPP, respectively. Ecosystem C stocks were mainly contributed by tree aboveground (39.9%-46.0%) and soil C stocks (41.6-44.2%). The ecosystem C density of SSP was higher than that of SPP and MPP, and significant differences were found among three plantations for both aboveground and underground C densities. The aboveground and underground ecosystem C storage of SSP was 27.4% and 53.4% higher than that of MPP, respectively. Meanwhile, root C storage of MPP was lower than that of SPP and SSP, while soil C storage of MPP was lower than that of SSP. In the understory layer, SPP had the highest C density, followed by MPP, and there was a significant difference in C density among three plantations. However, no significant difference was found for the ecosystem C distribution among three plantations. Our results show that vegetation types significantly affect C storage but not C distribution in forest ecosystems and establishing the broad-leaved plantation has the highest ecosystem C storage in the subtropics. This study provides a theoretical basis for us to choose appropriate forest management measures.